New approaches to QSAR: Neural networks and machine learning - King,RD; Hirst,JD; Sternberg,MJE (Perspectives in Drug Discovery and Design, 1993)
Neural networks and machine learning are two methods that are increasingly being used to model QSARs. They make few statistical assumptions and are nonlinear and nonparametric. We describe back-propagation from the field of neural networks, and GOLEM from machine learning, and illustrate their learning mechanisms using a simple expository problem. Back-propagation and GOLEM are then compared with multiple linear regression (using the parameters and their squares) on two real drug design problems: the inhibition of Escherichia coli dihydrofolate reductase (DHFR) by pyrimidines and the inhibition of rat/mouse tumour DHFR by triazines. © 1993 ESCOM Science Publishers B.V.